2014
DOI: 10.1039/c4cy00522h
|View full text |Cite
|
Sign up to set email alerts
|

Stability and resistance of nickel catalysts for hydrodeoxygenation: carbon deposition and effects of sulfur, potassium, and chlorine in the feed

Abstract: aThe long term stability and resistance toward carbon deposition, sulfur, chlorine, and potassium of Ni/ZrO 2 as a catalyst for the hydrodeoxygenation (HDO) of guaiacol in 1-octanol (as a model compound system for bio-oil) has been investigated at 250°C and 100 bar in a trickle bed reactor setup. Without impurities in the feed good stability of the Ni/ZrO 2 catalyst could be achieved over more than 100 h of operation, particularly for a sample prepared with small Ni particles, which minimized carbon deposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 67 publications
3
62
0
Order By: Relevance
“…As ZrO2 previously has been reported to exhibit a low activity at the current conditions [51] and Ni/ZrO2 is inactive for HDO under sulfiding conditions [7], the results in Table 2 reflect that the changes in activity must mainly be due to changes in the NiMoS2 phase.…”
Section: Inhibition Strength Of H2s H2o and Chlorinementioning
confidence: 78%
See 2 more Smart Citations
“…As ZrO2 previously has been reported to exhibit a low activity at the current conditions [51] and Ni/ZrO2 is inactive for HDO under sulfiding conditions [7], the results in Table 2 reflect that the changes in activity must mainly be due to changes in the NiMoS2 phase.…”
Section: Inhibition Strength Of H2s H2o and Chlorinementioning
confidence: 78%
“…The catalytic activity in an empty reactor was tested in connection with previous work on the same setup as used in this study and was found insignificant [7]. Repeatability was also tested in this study and a relative standard deviation for hydrodeoxygenation activity of 9% was found from a threefold repetition on the setup.…”
Section: Catalyst Testingmentioning
confidence: 96%
See 1 more Smart Citation
“…Given that carbon nanofibers and carbon nanotubes are respectively grown using Ni and Fe catalysts and that the hydrodeoxygenation of guaiacol has been reported to proceed over both Ni [19][20][21] and Fe [22][23][24] catalysts, the activity of the bare supports could conceivably be caused by the residual presence of these metals. Indeed, the Ni and Fe content of the carbon supports was measured by means of Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES) and determined to be non-negligible, as shown in Table 4.…”
Section: Catalyst Evaluation In Dodecanementioning
confidence: 99%
“…Recent HDO studies reported application of continuous flow reactors using organic solvents (e.g., 1-octanol, 1-octane, 1-hexane) [43][44][45] or supercritical water [46]. Those studies often have not put the focus on the spent catalysts after long-term reaction.…”
Section: Introductionmentioning
confidence: 99%